Chromatic Pupillometry Findings in Alzheimer’s Disease - Romagnoli, Martina; Stanzani Maserati, Michelangelo; De Matteis, Maddalena; Capellari, Sabina; Carbonelli, Michele; Amore, Giulia; Cantalupo, Gaetano; Zenesini, Corrado; Liguori, Rocco; Sadun, Alfredo A.; Carelli, Valerio; Park, Jason C.; et al. (Frontiers in Neuroscience, 2020)
Intrinsically photosensitive melanopsin retinal ganglion cells (mRGCs) are crucial for non-image forming functions of the eye including the photoentrainment of circadian rhythms and the regulation of the pupillary light reflex (PLR). Chromatic pupillometry can be used to asses mRGCs contribution to PLR by using light stimuli at different wavelengths. We previously demonstrated in post-mortem AD retinas the presence of mRGC loss and dendritic pathology. In this study, using chromatic pupillometry, we demonstrated in a cohort of mild-moderate AD patients the presence of transient PLR amplitude abnormalities that may reflect a pathology affecting mRGC dendrites before involving the mRGC cell body. This study highlights the potentiality of using pupillometry as a potential biomarker in AD. Further studies including more severe and with longer disease duration AD cases are needed to further understand mRGC pathology.